2007
DOI: 10.1016/j.bpc.2007.02.003
|View full text |Cite
|
Sign up to set email alerts
|

DOTAP/DOPE and DC-Chol/DOPE lipoplexes for gene delivery studied by circular dichroism and other biophysical techniques

Abstract: Cationic liposomes give rise to stable complexes with DNA molecules ( lipoplexes) that are of great interest for gene delivery applications. In particular, liposomes made up by a cationic lipid (DOTAP or DC-Chol) and a zwitterionic lipid (DOPE), produce stable adducts with single and double -stranded DNA oligonucleotides. Formation of these lipople xes has been further addressed here by circular dichroism spectroscopy (CD) and by other independent biophysical methods. Titration of DNA oligonucleotides with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 38 publications
1
27
0
1
Order By: Relevance
“…In the case of the hexacationic species 2a, 2b, 3a and 3b, the UV absorption at 260 nm was almost reduced to zero at r ¼ 0.5, indicating that nearly all of the DNA has precipitated, explaining the loss of the CD signal in these cases. Similar observations have been reported upon titration of DNA with cationic liposomes [37].…”
Section: Dna Interactions Of Oligocationic Phosphines and Their Ru Cosupporting
confidence: 73%
“…In the case of the hexacationic species 2a, 2b, 3a and 3b, the UV absorption at 260 nm was almost reduced to zero at r ¼ 0.5, indicating that nearly all of the DNA has precipitated, explaining the loss of the CD signal in these cases. Similar observations have been reported upon titration of DNA with cationic liposomes [37].…”
Section: Dna Interactions Of Oligocationic Phosphines and Their Ru Cosupporting
confidence: 73%
“…In the case of the DOPE:DSTAP lipoplexes, the presence of PBS was shown to significantly (p < 0.05) increase the size of the lipoplexes at all DNA concentrations and of the 4 formulations, DOPE:DSTAP in PBS gave the largest lipoplexes (Figure 4). Previous research has also shown the size of the liposomes can increase to double the size in the presence of PBS as the phosphate group of the PBS can perform as glue and increase the vesicle size by bridging the cationic polar heads of the lipid [21]. Another study reveals cationic liposomes have a higher tendency to aggregation when there is salt in the formulation due to the reduced electrostatic interactions between systems and consequently more aggregation and larger vesicles formed [37].…”
Section: Resultsmentioning
confidence: 99%
“…The electrostatic interaction between positive charges of the cationic liposome and negative charges of phosphate groups of DNA are reported as the main interaction in formation of lipoplexes [21,31]. Some other researchers add that packing properties of the lipids used in the formulation of lipoplexes may also play a role in condensation of the nucleic acid [40,41].…”
Section: Resultsmentioning
confidence: 99%
“…Gene transfection mediated by cationic liposomes was affected by numerous factors, including the compositions of the cationic liposomes. In addition, altering the type and amount of cationic lipids in the cationic liposomes can enhance the transfection efficiency (17,18). In this study, the effect of the chemical structure of the cationic lipids used for preparing liposomes and the weight ratios of liposomes/DNA on the transfection efficiency were evaluated in comparison with Lipofectamine™ 2000 (weight ratio of 2) and naked pDNA transfection (Fig.…”
Section: In Vitro Transfection In Hela Cellsmentioning
confidence: 99%